Choreographing problems: Expressive concepts in European contemporary dance and performance - Cvejic, Bojana (Palgrave Macmillan, 2015)
Choreographing Problems: Expressive Concepts in European Contemporary Dance and Performance illuminates the relationship between the philosophy of Gilles Deleuze and experimental dance and performance in the works of leading European choreographers, Xavier Le Roy, Jonathan Burrows, Boris Charmatz, Eszter Salamon, Mette Ingvartsen, Jefta van Dinther, and Jan Ritsema. Combining intricate analysis of seven groundbreaking works, including Self Unfinished by Le Roy (1998) and Weak Dance Strong Questions (2001) by Burrows and Ritsema, with a philosophical discussion of the body, movement and time in performance, as well as the notions of theatricality, affect, improvisation and process, the capacity of choreography to 'express' thought is unravelled. Choreographing problems involves composing ruptures between movement, the body and duration in performance such that they engender a shock upon sensibility, one that inhibits recognition. This book offers a practical insight into the matters of choreography: it allows both the versed and the non-trained spectator to observe in detail how the thought and the practices of making, performing and attending reinvent performance and dance today.